2017
DOI: 10.1021/acsami.7b06022
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Based on Easily Synthesized, Low Cost Triphenolate–Borohydride Salt for High Performance Mg(TFSI)2-Glyme Rechargeable Magnesium Batteries

Abstract: A new class of electrolyte based on TFSI and triphenolate-borohydride anions was designed and produced which fulfill all requirements of easy synthesis, high ionic conductivity, wide potential window, and noncorrosion of Al current collector. The electrolyte composed of magnesium triphenolate borohydride and Mg(TFSI) in glyme simultaneously displays a high conductivity of 5.5 mS cm at 25 °C and a reversible Mg plating/stripping with high current density and Coulombic efficiency at room temperature. By addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Also, the charge‐delocalized framework makes this conjugated [NTf 2 ] − anion highly resistant to positive potential polarization, and thus high anodic stability can be expected in such electrolytes. There have been a number of studies using Mg[NTf 2 ] 2 in different solvents for reversible Mg electrochemistry, particularly in polyether(s) ,. Electrolytes using 0.5 M Mg[NTf 2 ] 2 in a glyme/diglyme mixture showed a high conductivity of 5.2 mS cm −1 , and the anodic stability on stainless steel (SS) substrate was up to 4.2 V vs Mg …”
Section: Rechargeable Mg Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the charge‐delocalized framework makes this conjugated [NTf 2 ] − anion highly resistant to positive potential polarization, and thus high anodic stability can be expected in such electrolytes. There have been a number of studies using Mg[NTf 2 ] 2 in different solvents for reversible Mg electrochemistry, particularly in polyether(s) ,. Electrolytes using 0.5 M Mg[NTf 2 ] 2 in a glyme/diglyme mixture showed a high conductivity of 5.2 mS cm −1 , and the anodic stability on stainless steel (SS) substrate was up to 4.2 V vs Mg …”
Section: Rechargeable Mg Batteriesmentioning
confidence: 99%
“…There have been a number of studies using Mg[NTf 2 ] 2 in different solvents for reversible Mg electrochemistry, particularly in polyether(s). [43,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] Electrolytes using 0.5 M Mg[NTf 2 ] 2 in a glyme/diglyme mixture showed a high conductivity of 5.2 mS cm À1 , and the anodic stability on stainless steel (SS) substrate was up to 4.2 V vs Mg. [46] Glymes with higher oligomer degree exhibit stronger ability to solvate Mg[NTf 2 ] 2 . [43,51] For example, a higher solubility of Mg has been reported in tetraglyme (G4) than in diglyme (G2).…”
Section: Mg[ntf 2 ] 2 Electrolytesmentioning
confidence: 99%
“…Note that in the latter case, reaction of the reductive borohydride with the acidic additive was indicated thereby partially transforming the borohydride (further investigation is needed to identify the new species). Another approach that was applied to modify Mg(TFSI)2 solutions with BH4 − was using a BH4 − anion with hydride groups that were partially substituted with phenol [91]. Both 0.5 M Mg(TFSI)2 and 0.15 M Mg(B(OPh)3H)2 were combined in diglyme and exhibited low deposition overpotentials (ca −0.64 V); however, the coulombic efficiency remained at low as 64% even after extended cycling [91].…”
Section: Liquid Borohydride Electrolytes: Achieving Compatibility Witmentioning
confidence: 99%
“…− was using a BH 4 − anion with hydride groups that were partially substituted with phenol [91]. Both 0.5 M Mg(TFSI) 2 and 0.15 M Mg(B(OPh) 3 H) 2 were combined in diglyme and exhibited low deposition overpotentials (ca −0.64 V); however, the coulombic efficiency remained at low as 64% even after extended cycling [91].…”
Section: Liquid Borohydride Electrolytes: Achieving Compatibility Witmentioning
confidence: 99%
“…Also, Watanabe and co‐workers demonstrated that using molecular sieves to remove water impurities in tetraglyme solvents allows reversible Mg striping/plating . In light of the difficult access to very pure and dry Mg(TFSI) 2 and ether solvents, the introduction of an “impurity scavenger” (such as MgCl 2 , Mg(BH 4 ) 2 , Bu 2 Mg, or triphenolate‐borohydride) has been demonstrated to be an effective strategy to achieve highly reversible Mg stripping/plating processes (Table ) . By adding these highly reactive or reductive reagents, the extremely reduced overpotential for Mg deposition and stripping processes could be achieved as expected due to the consumption of water impurities.…”
Section: Recent Mg‐ion Electrolyte Advancesmentioning
confidence: 99%